Volume 1B: Marine; Microturbines, Turbochargers and Small Turbomachines; Steam Turbines 2014
DOI: 10.1115/gt2014-25177
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of the Impact of Part-Span Connectors on Aero-Thermodynamics in a Low Pressure Industrial Steam Turbine

Abstract: A numerical study on the flow in a three stage low pressure industrial steam turbine with conical friction bolts in the last stage and lacing wires in the penultimate stage is presented and analyzed. Structured high-resolution hexahedral meshes are used for all three stages and the meshing methodology is shown for the rotor with friction bolts and blade reinforcements. Modern three-dimensional CFD with a non-equilibrium wet steam model is used to examine the aero-thermodynamic effects of the part-span connecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 0 publications
1
20
1
Order By: Relevance
“…Maier 4 reported an efficiency drop of two percentage points due to cylindrical damping pins in LP rotor blades, which was investigated by means of performance measurements with and without the PSCs in a model steam turbine, whereby the vibrational behavior of the configurations as well as geometric details of the PSCs and the test rig are described by Pfeiffer. 5 The results of Maier 4 are in reasonable correlation to the outcome of Ha¨fele et al, 1 as the relation of flow channel area blocked by the PSCs to efficiency drop is similar.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…Maier 4 reported an efficiency drop of two percentage points due to cylindrical damping pins in LP rotor blades, which was investigated by means of performance measurements with and without the PSCs in a model steam turbine, whereby the vibrational behavior of the configurations as well as geometric details of the PSCs and the test rig are described by Pfeiffer. 5 The results of Maier 4 are in reasonable correlation to the outcome of Ha¨fele et al, 1 as the relation of flow channel area blocked by the PSCs to efficiency drop is similar.…”
Section: Introductionsupporting
confidence: 79%
“…The general vortex structure in rotor R3 with friction bolt (FB) and blade reinforcements (BR) was already described by Ha¨fele et al 1 and a discussion of the vortex structure in rotor R2, where a simple lacing wire is installed, can be found in Ha¨fele et al 7 For all configurations investigated in the present study the vortex structure induced by the PSC in rotor R3 can be divided into three different main vortices (see Figures 8 and 9), whereby their size, interaction and orientation varies depending on the PSC geometry. Out of the three vortices, the vortex at the blade suction side (PSC vortex SS) is the biggest one.…”
Section: Performance Assessment Of Psc Designsmentioning
confidence: 98%
See 1 more Smart Citation
“…CFD flow research methods based on boundary conditions found in experimental steam turbines are a rather common form of flow research in last stages and exhaust hoods [10,11].…”
Section: Cfd Setupmentioning
confidence: 99%
“…A common problem in the last stages of low-pressure (LP) steam turbines is "condensation shock" that can be interpreted as a non-equilibrium and unsteady thermodynamic phenomenon. Due to the negative effects of condensation on the performance of steam turbines, this phenomenon has been investigated in many studies both numerically [19][20][21][22][23] and experimentally [24][25][26][27][28][29]. During the expansion of steam, under certain circumstances in LP steam turbines, the one-phase vapor changed into a two-phase mixture after supercooling and nucleation.…”
Section: Introductionmentioning
confidence: 99%